Freshwater biota and rising pCO2?. (27th November 2015) - Hasler, Caleb T.; Butman, David; Jeffrey, Jennifer D.; Suski, Cory D.
Abstract: Rising atmospheric carbon dioxide (CO2 ) has caused a suite of environmental issues, however, little is known about how the partial pressure of CO2 (pCO2 ) in freshwater will be affected by climate change. Freshwater pCO2 varies across systems and is controlled by a diverse array of factors, making it difficult to make predictions about future levels of pCO2 . Recent evidence suggests that increasing levels of atmospheric CO2 may directly increase freshwater pCO2 levels in lakes, but rising atmospheric CO2 may also indirectly impact freshwater pCO2 levels in a variety of systems by affecting other contributing factors such as soil respiration, terrestrial productivity and climate regimes. Although future freshwater pCO2 levels remain uncertain, studies have considered the potential impacts of changes to pCO2 levels on freshwater biota. Studies to date have focused on impacts of elevated pCO2 on plankton and macrophytes, and have shown that phytoplankton nutritional quality is reduced, plankton community structure is altered, photosynthesis rates increase and macrophyte distribution shifts with increasing pCO2 . However, a number of key knowledge gaps remain and gaining a better understanding of how freshwater pCO2 levels are regulated and how these levels may impact biota, will be important for predicting future responses to climate change.